Cryptographic security solutions for the Internet of Things - Banday, Mohammad Tariq, 1969- (Information Science Reference, an imprint of IGI Global, 2019)
"This book discusses novel designs and recent developments in the field of low power, low resource cryptographic security control procedures to improve the efficiency of existing security mechanisms that can help in securing sensors, devices, networks, communication and data in the internet of things"--